Improving communication in the emergency department. Issue 9 (21st August 2009) - Redfern, E; Brown, R; Vincent, C A
Abstract : Background: A previous study examined the communication process within the emergency department (ED) and identified a complex process with many opportunities for breakdown and error. In this paper the first two interventions in a series of studies to improve this highly vulnerable communication process are described. Aim: To improve the reliability of two steps of the communication process identified as having a high probability of failure: (1) transfer of information between the ambulance crew and the emergency staff; and (2) preparation of written documentation following patient assessment. Methods: Quantitative assessments of the reliability of communication were carried out to establish the extent of problems highlighted during the failures modes and effects analysis (FMEA) previously described. Improvements to the process were then introduced, and the process re-examined to assess the impact of the changes and reduction of the likelihood and severity of the failure mode. Results: The studies demonstrated very high levels of communication failure, particularly in transfer of written information from the ambulance crew. Countermeasures were introduced which resulted in a substantial reduction in missing and incorrect information. In addition, there was a threefold improvement in the number of correct clinical documents used by doctors in the resuscitation room. Conclusion: Observational study and audit revealed the extent of process failures identified in the initial FMEA process. With the introduction of simple changes to the communication system, a marked improvement in the availability and quality of pertinent clinical information was achieved with considerable implications for the timeliness and quality of care provided to patients.